Impact of postoperative antibiotics on rates of infection and implant removal after tibial tuberosity advancement in 1, 768 canine stifles. Issue 5 (5th June 2019) - Ferrell, Christopher L.; Barnhart, Matthew D.; Herman, Eric
Abstract: Objective: To report infection rate, implant removal rate, and postoperative antibiotic therapy after tibial tuberosity advancement (TTA) in dogs. Study design: Retrospective study. Animals: One thousand seven hundred sixty‐eight stifles in 1, 732 dogs. Methods: Medical records (January 2007‐December 2011) of dogs treated with a TTA were reviewed. Cases were included if at least 1 year of postoperative follow‐up was available and no additional procedures were performed on the stifle. Date of surgery, date of culture, culture and susceptibility results, postoperative antimicrobials used, and any implant removals were recorded. Use of postoperative antibiotics and implant removal were evaluated statistically for effect on infection occurrence and resolution. Results: Postoperative infections were diagnosed in 82 of 1, 768 (4.6%) stifles. Implants were removed from 32 (39%) stifles, with plate and screw removal only in 23 (71.9%) stifles. The rate of infection did not differ between dogs with or without postoperative antibiotic therapy. However, dogs receiving postoperative antibiotic therapy were at risk for developing an oxacillin‐resistant infection ( P = .001). Oxacillin‐resistant infections were associated with a requirement for implant removal to achieve resolution compared with other types of bacterial infections ( P < .05). Conclusion: No benefit was detected with the use of postoperative antibiotics after TTA in this population. Implant removal was infrequent, and the requirement for cage removal was not commonly required for infection resolution. Clinical significance: This study does not provide evidence to support postoperative antibiotic therapy after TTA. Postoperative infection can be treated in most dogs without removal of the TTA cage.